Clinico-epidemiological profile of HIV patients attending ART centre in rural Western Maharashtra, India - Deshpande, Jayant D; Giri, Purushottam A; Phalke, Deepak B (South East Asia Journal of Public Health, 2013)
HIV infection represents a major public health problem for both developing and developed countries as it has grown to pandemic proportions worldwide. Spectrum of clinical presentation of HIV can vary with geographical distribu-tion, socioeconomic and cultural environment. The aim of this study was to examine the socio-demographic charac-teristics, clinical presentations of HIV/AIDS patients, opportunistic infections and the possible risk factors for ac-quiring HIV infection. A cross sectional study was conducted from March to September, 2011 at an antiretroviral therapy (ART) centre of a rural tertiary care hospital, situated in Maharashtra state of India. History and physical examination was done and recorded on a pre-designed schedule which included the socio-demographic and clinical profile of the patients. More than half of the subjects were in economically productive age group and male patients 166 (53.4%) outnumbered the female patients 145 (46.6%). There was a predominance of patients from rural loca-tions nearby the present ART centre. The patients were having low level of literacy and were from the lower middle and lower socio-economic classes. Among the spouses of male patients, 65 (44.8%) were HIV positive and among the spouses of female patients, 52 (35.7%) were HIV positive. Commonest mode of acquiring the infection was through heterosexual contact. Tuberculosis (62%) was the most common opportunistic infection. As per the WHO staging, 132 (42.5%) patients were in stage 3. Combination of behavioral risk factors and unawareness is responsi-ble for rapid spread of HIV/AIDS. People with high-risk behavior and spouses of affected patients need to be edu-cated for primary and secondary prevention. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15938 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 16-21